Patient‐reported outcomes and inflammatory biomarkers in patients with locally advanced/metastatic urothelial carcinoma treated with durvalumab in phase 1/2 dose‐escalation study 1108. Issue 2 (3rd October 2019) - O'Donnell, Peter H.; Arkenau, Hendrick Tobias; Sridhar, Srikala S.; Ong, Michael; Drakaki, Alexandra; Spira, Alexander I.; Zhang, Jingsong; Gordon, Michael S.; Degboe, Arnold N.; Gupta, Ashok K.; Mukhopadhyay, Pralay; Huang, Wenmei; et al.
Abstract : Background: Durvalumab has shown meaningful clinical activity in patients with metastatic urothelial carcinoma (mUC) in Study 1108 (NCT01693562). An important focus in treatment is health‐related quality of life (HRQOL). Here, patient‐reported outcomes (PROs) from Study 1108 and their relationship with inflammatory biomarkers are explored. Methods: Disease‐related symptoms, functioning, and HRQOL were assessed with the Functional Assessment of Cancer Therapy–Bladder (FACT‐Bl) and the European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire Core 30 (QLQ‐C30). Relationships between PRO improvements and the best changes in the tumor size, albumin level, and neutrophil‐lymphocyte ratio (NLR) were assessed with Spearman correlation analysis. Results: The mean FACT‐Bl total score improved from 107.5 (standard deviation [SD], 23.0) at the baseline to 115.4 (SD, 22.6) on day 113, with similar increases found for the Trial Outcome Index (TOI) and Bladder Cancer Subscale (BLCS) scores. The mean FACT‐Bl total scores improved over time, and the FACT‐Bl TOI scores significantly improved by day 113 ( P < .05). The mean EORTC QLQ‐C30 Global Health Status/Quality of Life score improved from 57.1 (SD, 24.8) at the baseline to 69.0 (SD, 21.4) on day 113; the functional scale and symptom scores (day 113) were higher than the baseline scores ( P < .05) for EORTC Social Functioning. The FACT‐Bl total, BLCS, and TOI scores improved in 32.6%, 34.9%, and 32.6% of the patients by day 113; 26.3% to 37.8% of the patients exhibited improvements in EORTC QLQ‐C30 functional scores. The best tumor shrinkage and posttreatment improvements in serum albumin and NLR correlated with increases in FACT‐Bl total, TOI, and BLCS scores and in EORTC Physical Functioning and Role Functioning scores ( P < .05). Conclusions: Durvalumab was associated with improvements in disease‐related symptoms, functioning, and HRQOL in patients with mUC. Improvements in systemic inflammation may contribute to PRO improvements in these patients. Abstract : In patients with locally advanced/metastatic urothelial carcinoma treated with durvalumab, improvements in patient‐reported outcomes correlate not only with objective tumor responses but also with reductions in markers of systemic inflammation. These findings provide insight into potential links between attenuation of inflammation in cancer and patient‐reported outcomes.